2012
DOI: 10.1080/2159676x.2011.653501
|View full text |Cite
|
Sign up to set email alerts
|

Exercise, service and support: client experiences of physical activity referral schemes (PARS)

Abstract: Physical Activity Referral Schemes (PARS) continue to represent one of the most prevalent interventions in the fight against chronic illness such as Coronary Heart Disease (CHD) and obesity. Despite this, issues surrounding low retention and adherence continue to hinder the potential effectiveness of such schemes on public health. This article reports on the second stage of a larger investigation into client experiences of PARS focussing specifically on findings from five client focus groups and interviews wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The research design adopted is noteworthy in that it contrasts with other studies in the exercise referral literature in 2 specific ways. Firstly, the majority of studies published in this area adopt a quantitative approach [28][29][30][31][32][33], although some studies do adopt a qualitative approach [34][35][36][37]. Through using a qualitative approach to data collection and analysis, this study was able to investigate the patients' experiences of involvement with an exercise referral scheme and its impact on sustaining physical activity levels for 3 months after completion of the programme.…”
Section: Methods Designmentioning
confidence: 99%
“…The research design adopted is noteworthy in that it contrasts with other studies in the exercise referral literature in 2 specific ways. Firstly, the majority of studies published in this area adopt a quantitative approach [28][29][30][31][32][33], although some studies do adopt a qualitative approach [34][35][36][37]. Through using a qualitative approach to data collection and analysis, this study was able to investigate the patients' experiences of involvement with an exercise referral scheme and its impact on sustaining physical activity levels for 3 months after completion of the programme.…”
Section: Methods Designmentioning
confidence: 99%
“…The research design adopted is noteworthy in that it contrasts with other studies in the exercise referral literature in 2 specific ways. Firstly, the majority of studies published in this area adopt a positivist approach [21][22][23][24][25], although some studies do adopt an interpretive approach [26][27][28][29]. Through using a qualitative approach to data collection and analysis, this study was able to investigate the patients' changing perceptions over a 6-month time period for the following QoL indicators of (i) self-efficacy, (ii) selfmanagement, (iii) chronic fatigue and (iv) increasing energy levels [12,16,18].…”
Section: Methods Designmentioning
confidence: 99%
“…Previous findings from both qualitative [15,18,20,25] and quantitative [23,27,28,32] research in exercise referral has shown that ERS can promote physical activity in the short to medium-term (12-26 weeks). In our analysis of 12 seriously ill patients participating in an ERS, we found that long-term engagement with a practice-based scheme aided physical activity adherence and increased combined (walking and exercise classes) physical activity levels, in the long-term.…”
Section: Discussionmentioning
confidence: 99%
“…The study design contrasts with other studies on exercise referral in 3 specific ways. First, the majority of studies on exercise referral tend to be from a positivist theoretical perspective [20][21][22][23][24], rather than an interpretivist perspective [15,17,18,25]. Second, the deployment of 3 data collection and analysis phases differed to traditional schemes that have a 12 week intervention [15,[26][27][28][29][30] and a 12 week follow up [31,32].…”
Section: E T Hod De Signmentioning
confidence: 99%
See 1 more Smart Citation